2020
DOI: 10.12659/ajcr.923197
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Bleeding in a Pancreas Transplant Recipient: A Case to Remember

Abstract: Patient: Male, 51-year-old Final Diagnosis: Ectopic varix Symptoms: Bleeding • portal hypertension Medication:— Clinical Procedure: — Specialty: Transplantology Objective: Unusual clinical course Background: Pancreas transplantation has proven to be the most effective therapeutic option for insulin-dependent diabetes mellitus. However, despite advances in surgical technique and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…The complication of varices of anastomosis between the native jejunum and the duodenal graft after the PTx is rare and has been reported in only 3 case studies summarized in Table 1. [1][2][3] The onset times in these studies were 1, 4, 5, and 14 years (our case) after the PTx, which suggested that this complication developed relatively slowly after the PTx. In addition, in 3 of the 4 cases, embolization was successful, which suggested that embolization might be a clinically effective treatment for varices after a PTx.…”
mentioning
confidence: 50%
“…The complication of varices of anastomosis between the native jejunum and the duodenal graft after the PTx is rare and has been reported in only 3 case studies summarized in Table 1. [1][2][3] The onset times in these studies were 1, 4, 5, and 14 years (our case) after the PTx, which suggested that this complication developed relatively slowly after the PTx. In addition, in 3 of the 4 cases, embolization was successful, which suggested that embolization might be a clinically effective treatment for varices after a PTx.…”
mentioning
confidence: 50%
“…Four case reports detail patients with variceal bleeding in the setting of prior pancreas transplant 4–6,10 . Two of the four patients underwent embolization with sodium tetradecyl sulfate, one of whom died of myocardial infarction shortly after 6 and the other required additional embolization procedures for ongoing bleeding, ultimately requiring bowel resection, and also experienced non‐occlusive portal vein thrombosis 5 . In one case, the patient underwent coil embolization with durable effect and no reported bowel ischemia 4 .…”
Section: Discussionmentioning
confidence: 99%
“…4,9 To our knowledge, there are only four reported cases in the literature of ectopic varices causing gastrointestinal hemorrhage following pancreatic transplant. [4][5][6]10 We present two patients with remote history of SPK who presented with anemia and melena found to be secondary to bleeding ectopic varices.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations